A risk-based design of ammonia refrigeration systems in food manufacturing plants - Biscotti, Paola Silvina (2019)
This paper presents a risk-based design procedure of ammonia based refrigeration processes taking into account the allocation of the manufacturing plant and the surrounding environment vulnerability at early stages of process design. In addition, the proposed design framework allows the integration of a process simulator with vulnerability assessment packages. As a case study, the design of the refrigeration system for a surimi manufacturing plant is presented.